Assembling interferometers and in-situ observation of ambient environments and solid–liquid interfaces. Issue 2 (June 2016) - Kimura, Yuki; Murayama, Kenta; Yamazaki, Tomoya; Maki, Takao
Abstract: The principle of interferometers and its applicability to our research on crystal growth can be understood through assembling interferometers. In particular, practical skills such as techniques for assembling interferometers and selecting optical components, which are not covered by general textbooks, can be learned.